PERSEPSI MAHASISWA TERHADAP PENGGUNAAN MEDIA WHATSAAP DAN GOOGLE CLASROOM DALAM PEMBELAJARAN DARING MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS COKROAMINOTO PALOPO - eva sohriati (Universitas Cokroaminoto Palopo, 2021)
One of the efforts to prevent the spread of Covid-19 in the educational environment, the Ministry of Education and Culture, responded with a